scarica il file .RTF compresso in formato .ZIP

Sei equazioni di 1 grado senza frazioni

Equazione 1

10 (x + 2) + 20 = 6 (x - 2) + 22 - x

Equazione 2

Equazione 3

Equazione 4

Equazione 5

Equazione 6

Soluzione 1

10 (x + 2) + 20 = 6 (x - 2) + 22 - x

 10x + 20 = 6x - 12 + 22 - x
10x + x - 6x = -12 + 22 - 20
5x = -30
x = (-30)/(5) = -6 

verifica

10 [(-6) + 2] + 20 = 6 [(-6) - 2] + 22 - (-6)
10 (-6 + 2) + 20 = 6 (-6 - 2) + 22 + 6
10 (-4) + 20 = 6 (-8) + 22 + 6
-40 + 20 = - 48 + 22 + 6
-20 = -26 +6
-20 = - 20
verificata 

 

Soluzione 2

2x - 5x +6x = 40 - 28 
3x = 12 
x = (12)/(3) = +4 

Verifica

2(4)+28 = 40 + 5(4) - 6(4)
8+28 = 40 + 20 - 24
36 = 36
verificata 
 

Soluzione 3

 

2x + 12x -6x -5x = 40 -28
3x = 12 

x = 12/3 

x = 4  2(4) + 12(4) + 28 = 6(4) +40 + 5(4) 
8 + 48 + 28 = 24 +40 + 20
84 = 84 

verificata 


 

Soluzione 4

-12 - 4x - 14x - 28 + 15 = - 15 - 8x
- 4x - 14x + 8x = - 15 + 12 + 28 - 15
-10x = + 10
x = (-10)/(10) = -1

Verifica 4

4 [-3 - (-1)] - 14 [(-1) + 2] + 15 = - 15 - 8(-1)
4 (-3 +1) - 14 (-1 + 2) + 15 = - 15 + 8
4 (-2) - 14 (1) + 15 = - 7
-8 - 14 + 15 = - 7
-7 = - 7
verificata 

Soluzione 5



6x - 3 - 5x - 20 = -6x - 2 
6x + 6x - 5x = + 3 + 20 - 2 
7x = +21
x = (21)/(7) = +3  3[2(3)-1]-5[(3)+4]= -2[3(3)+1]
3(6-1)-5(3+4)= -2(9+1)
3(5)-5(7)= -2(10)
15 - 35 = -20
15 - 35 = -20
-20 = - 20
verificata 

Soluzione 6


 
4x - 9 + 2 x + 6 = 3x + 3
 4x + 2 x - 3x = 3 + 9 - 6
 3x = 6
 x = 2 

8-9+2(5) = 3(3) 

9 = 9 

verificata